2016
DOI: 10.1590/1516-635x1801181-186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arginine Supplementation on Organ Development, Egg Quality, Serum Biochemical parameters, and Immune Status of Laying Hens

Abstract: This experiment was conducted to study the effects of arginine supplementation on organ development, egg quality, blood parameters, and immune status of laying hens. A total of 360 25-week-old brown Leghorn laying hens were randomly divided into three groups with six replicates of 20 birds each and fed diets supplemented with 0, 8.5, or 17 mg of L-arginine/kg for 42 days. Results showed that the weight of proventriculus and duodenum in the treatment supplemented with 17 mg/kg L-arginine was heavier than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…(2010), Fouad, El‐Senousey, Yang, and Yao (2013) and Yang et al. (2016) in chickens suggest that Arg supplementation exceeding the NRC recommendation (1994) may reduce TC blood levels. According to Fouad et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2010), Fouad, El‐Senousey, Yang, and Yao (2013) and Yang et al. (2016) in chickens suggest that Arg supplementation exceeding the NRC recommendation (1994) may reduce TC blood levels. According to Fouad et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, since nitric oxide level was not affected by GAA supplementing, thus it is reasonable that lipid profile is not also affected. Considering liver enzymes in serum, Yang et al [19] showed that dietary inclusion of arginine significantly reduced levels of liver aspartate aminotransferase in laying hens. The increased aspartate aminotransferase in blood is considered as index for muscle and liver damages, which its levels are different in various birds [38] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, arginine reduces abdominal lipid and balances lipid storage by nitric oxide synthesis [18] . Yang et al [19] showed that dietary inclusion of arginine significantly reduced levels of liver aspartate aminotransferase in laying hens, implicating that arginine reduces liver damages. GAA is able to sparing body pool of arginine which is used for creatine synthesis [20] since it is converted to creatine in bird's kidney and liver [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The higher concentration of serum total protein in arginine supplemented groups could be possibly associated with higher demand for lean tissue maintenance and turnover [6]. Moreover, increased globulin fraction in arginine supplemented groups might be due to increased immune response [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that 0.25 % Larginine supplementation in the diets of broiler chickens reduced the blood plasma, total cholesterol and triglyceride concentrations [5]. Recent evidences about argnine supplementation were reported by [6] that lowered total serum cholesterol and triglyceride levels in the hens supplemented with 8.5 mg Larginine / kg diet than those of hens in the 0 mg L-arginine / kg diet. Hence, the study was designed and evaluated by supplementing different levels of arginine on serum biochemical parameters in broiler chicks.…”
Section: Introductionmentioning
confidence: 96%